Erythrocyte changes and ecotoxicological evaluation in freshwater of the Pintado stream in the municipality of Ji-Paraná, Brazil: Anurans of the genus Leptodactylus (Leptodactilidae) as a bioindicator organism - Jacqueline Lopes dos Santos; Patrícia Pastana de Sousa; Natália Faria Romão; Matheus Venancio de Paula; Ana Carolina Anchieta Adriano; Sandro de Vargas Schons; Jerônimo Vieira Dantas Filho; Francisco Carlos da Silva (Acta Scientiarum: Biological Sciences)
The main aimed of this study was to conduct out an ecotoxicological assessment through the Micronucleus (Mn) test and other associated anomalies in peripheral erythrocyte cells, using the amphibian of the genus Leptodactylus as a bioindicator organism, in addition to analyzing the physicochemical parameters in freshwater of the Pintado stream located in urban perimeter of Ji-Paraná municipality, Rondônia State, Brazil. Sample collections were conducted out at three different points along the stream. The results obtained showed that the animals at points 2 and 3 had a higher frequency of Mn compared to point 1, indicating that there is exposure of the organisms to genotoxic and mutagenic agents has been undergoing changes at the cellular level. The physicochemical results in the water, according to CONAMA Resolution No. 357/2005, that the parameters iron, ammonia nitrogen, dissolved oxygen and electrical conductivity showed high values at monitored points 2 and 3.